Applications of de-oiled microalgal biomass towards development of sustainable biorefinery. (August 2016) - Maurya, Rahulkumar; Paliwal, Chetan; Ghosh, Tonmoy; Pancha, Imran; Chokshi, Kaumeel; Mitra, Madhusree; Ghosh, Arup; Mishra, Sandhya
Graphical abstract: Highlights: Strategies for the valorisation of de-oiled microalgal biomass (DMB) are reviewed. Different processes to further recover energy from DMB are outlined. Use of DMB hydrolysate as a nutrient source for biological growth are described. Direct DMB utilization without pre-treatments are illustrated. Reviewed insights and perspectives on future applications of DMB. Abstract: In view of commercialization of microalgal biofuel, the de-oiled microalgal biomass (DMB) is a surplus by-product in the biorefinery process that needs to be exploited to make the process economically attractive and feasible. This DMB, rich in carbohydrates, proteins, and minerals, can be used as feed, fertilizer, and substrate for the production of bioethanol/bio-methane. Further, thermo-chemical conversion of DMB results into fuels and industrially important chemicals. Future prospects of DMB also lie with its conversion into novel biomaterials like nanoparticles and carbon-dot which have biomedical importance. The lowest valued application of DMB is to use it for adsorption of dyes and heavy metals from industrial effluents. This study reviews how DMB can be utilized for different applications and in the generation of valuable co-products. The value addition of DMB would thereby improve the overall cost economics of the microalgal bio-refinery.